Evaluation of herbal medicinal products perspectives on quality, safety, and efficacy - Mukherjee, Pulok K.; Houghton, Peter J. (Pharmaceutical Press, 2009)
"This book presents a structural approach to the evaluation of herbal medicinal products for quality, safety and efficacy. There has been an enormous growth in the market for herbal medicinal products in the last twenty five years. However the rediscovery of natural substances with therapeutic potential has raised questions of quality, safety and efficacy on the part of the consumer and also from health professionals. This book brings together current thinking and practice in these areas highlighting current research. In the light of increasing legislation to enforce better standards for these products and the demand by legislators and the public for assurance of safe and effective use, this book seeks to provide a state-of-the-art review, which informs and guides those who seek to promote their use. This book also gives an overview of the place of ethno pharmacology in the development of herbal medicinal products and discusses good agricultural and collection practices, marker analysis and stability testing which contribute to assessment of good quality of these materials." -- Publisher description.